Liver‐related mortality in countries of the developed world: an ecological study approach to explain the variability. Issue 1 (17th May 2016) - von Wulffen, M.; Clark, P. J.; Macdonald, G. A.; Raj, A. S.; Kendall, B. J.; Powell, E. E.; Jones, M. P.; Holtmann, G.
Summary: Background: Liver‐related mortality varies across developed nations. Aim: To assess the relative role of various risk factors in relation to liver‐related mortality in an ecological study approach. Methods: Data for liver‐related mortality, prevalence data for hepatitis B and C, human immunodeficiency virus (HIV), alcohol consumption per capita, Type 2 Diabetes mellitus (T2DM), overweight and obesity were extracted from peer‐reviewed publications or WHO databases for different developed countries. As potential other risk‐modifying factors, purchase power parity (PPP)‐adjusted gross domestic product (GDP) per capita and health expenditure per capita were assessed. As an environmental 'hygiene factor', we also assessed the effect of the prevalence of Helicobacter pylori . Only countries with a PPP‐adjusted GDP greater than 20 000 and valid information for at least 8 risk modifiers were included. Univariate and multivariate analyses were utilised to quantify the contribution to the variability in liver‐related mortality. Results: The proportion of chronic liver diseases (CLD)‐related mortality ranged from 0.73–2.40% [mean 1.56%, 95% CI (1.43–1.69)] of all deaths. Univariately, CLD‐related mortality was significantly associated with Hepatitis B prevalence, alcohol consumption, PPP‐adjusted GDP (all P < 0.05) and potentially H. pylori prevalence ( P = 0.055). Other investigated factors, including hepatitis C, did not yield significance. Backward elimination suggested hepatitis B, alcohol consumption and PPP‐adjusted GDP as risk factors (explaining 66.3% of the variability). Conclusion: Hepatitis B infection, alcohol consumption and GDP, but not hepatitis C or other factors, explain most of the variance of liver‐related mortality.